Determinant of Adolescent Sexual Behavior In West Nusa Tenggara Province (2015 RPJMN Data Analysis) - Mutiara Rachmawati Suseno; Mika Sandralina; Fitra Arsy Nurcory'ah (Universitas STRADA Indonesia, 2021)
Adolescent problems are very complex problems ranging from a large number to the problem of TRIAD KRR (Adolescent Reproductive Health) and the increasing number of births among adolescents (15-19 years). The National Population and Family Planning Board (BKKBN) stated that the birth rate among girls is still high, around 48 per 1,000 women.To determine the determinants of sexual behavior among adolescents in West Nusa Tenggara Province. This study is a cross-sectional study using secondary data from BKKBN survey. The sample was 42,469 adolescent respondents. The data analysis used was regression test.Multivariate analysis showed that age was a dominant factor in adolescent sexual behavior (p value = 0.000; OR = 3.123 95% CI = 2.526-3.86).The determinants that influence adolescent sexual behavior are level of education, age, knowledge of HIV and place of residence.